2022
DOI: 10.2147/pgpm.s351658
|View full text |Cite
|
Sign up to set email alerts
|

Associations of SMAD4 rs10502913 and NLRP3 rs1539019 Polymorphisms with Risk of Coal Workers’ Pneumoconiosis Susceptibility in Chinese Han Population

Abstract: Purpose CWP is an untreatable but preventable fibrotic lung disease caused by the chronic inhalation of coal dust. Genetic factors such as polymorphisms play an important role in the development of CWP. The present study investigated the association between the polymorphisms of SMAD4 and NLRP3 and CWP risk in a Chinese Han population. Patients and Methods SMAD4 rs10502913 and NLRP3rs1539019 polymorphisms were examined in 292 CWP subjects and 315 coal dust-exposed contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A case-control study indicated that the G allele of SMAD4 rs10502913 did not alter the risk of CWP compared with the A allele, and the GG genotypes did not increase the CWP risk compared with the AA genotype. 13 Another study based on the Health Professionals Follow-up and Nurses’ Health Study in the United States showed there is no association between SMAD4 rs10502913 polymorphism and type 2 diabetes risk. 35 However, it is still unclear which signaling pathways or target genes SMAD4 rs10502913 acts through, and further studies are needed to clarify its molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study indicated that the G allele of SMAD4 rs10502913 did not alter the risk of CWP compared with the A allele, and the GG genotypes did not increase the CWP risk compared with the AA genotype. 13 Another study based on the Health Professionals Follow-up and Nurses’ Health Study in the United States showed there is no association between SMAD4 rs10502913 polymorphism and type 2 diabetes risk. 35 However, it is still unclear which signaling pathways or target genes SMAD4 rs10502913 acts through, and further studies are needed to clarify its molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SMAD4 rs10502913 genotypes had no interaction with CWP risk in a stratified analysis of smokers and never-smokers. 13 However, the functionality of SMAD4 rs10502913 SNP in COPD has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%